Analysis of Antibiotic Consumption by AWaRe Classification in Shandong Province, China, 2012–2019: A Panel Data Analysis - Yin, Jia; Li, Hongyu; Sun, Qiang (Frontiers in Pharmacology, 2021)
Introduction: This study aims to examine the changes in trends and patterns of clinical consumption of antibiotics in Shandong, China based on Access, Watch, and Reserve (AWaRe) Classification after 10-year national antibiotic stewardship. Methods: Antibiotic consumption data of all health care institutions for the period 2012-2019 were obtained from the Drug Centralized Bidding Procurement System of Shandong. Shandong is a province that has the second-largest population in China. 5 of 16 cities in Shandong were grouped into high-income areas (HIAs) and the other 11 cities were grouped into upper middle-income areas (UMIAs). The main outcome measures were the antibiotic consumption rates (DDD per 1000 inhabitants per day, DID) and the proportions of different groups of antibiotics. Results: The overall antibiotic consumption rate increased from 12.859 to 15.802 DID between 2012 and 2014, then continuously decreased to 9.771 DID in 2019. The consumption rate of access, watch, and reserve antibiotics have reduced since 2014 with a compound annual growth rate of -10.1%, -9.0%, and -8.1%, respectively. During 2012-2019, the proportion of the access group reduced from 50.0% to 44.9%, while the proportion of the watch group increased from 42% to 45.2%. The antibiotic consumption rate has increased from 2012 to 2019 (from 7.38 to 9.12 DID) in the HIAs but has sharply decreased in the UMIAs from 2014 to 2019 (from 17.94 to 10.05 DID). The watch antibiotics had the largest proportion of consumption in the HIAs (55.3% in 2019), while the access group was the mostly consumed in the UMIA (49.5% in 2019). Conclusions: The antibiotic stewardship policies launched in the last ten years have contributed to reducing the clinical antibiotic consumption in Shandong. These policies have different effects on areas with different economic levels. The pattern of antibiotic consumption is still inappropriate in China as the watch group of antibiotics was consumed the most.